2019
DOI: 10.3390/pharmaceutics11050243
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterization of Inulin Conjugate for Improved Intracellular and Targeted Delivery of Pyrazinoic Acid to Monocytes

Abstract: The propensity of monocytes to migrate into sites of mycobacterium tuberculosis (TB) infection and then become infected themselves makes them potential targets for delivery of drugs intracellularly to the tubercle bacilli reservoir. Conventional TB drugs are less effective because of poor intracellular delivery to this bacterial sanctuary. This study highlights the potential of using semicrystalline delta inulin particles that are readily internalised by monocytes for a monocyte-based drug delivery system. Pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 67 publications
(75 reference statements)
2
17
0
Order By: Relevance
“…As expected, the INH thermogram is characterized by a single major thermal event (major decomposition) starting around 170 °C and finishing around 300 °C [77]. Inulin microparticles display typical three-step mass loss as reported in the literature [49,78]. The first stage weight loss of about 7% is attributed to the loss of water residue, followed by 51% major weight loss due to the inulin decomposition.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…As expected, the INH thermogram is characterized by a single major thermal event (major decomposition) starting around 170 °C and finishing around 300 °C [77]. Inulin microparticles display typical three-step mass loss as reported in the literature [49,78]. The first stage weight loss of about 7% is attributed to the loss of water residue, followed by 51% major weight loss due to the inulin decomposition.…”
Section: Resultsmentioning
confidence: 61%
“…The inulin particles are made exclusively from very short polymer chains typically isolated at ~40 fructose units and up to 100 units by the annealing conditions [53]. The microparticles are normally between 1 and 2 μm diameter [49,51,54].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inulin propionate esters showed an appetite-suppressing effect by suppressing energy intake and stimulating the release of satiety hormones, thus preventing weight gain [33]. The conjugation of inulin with some antibiotic drugs proved to be favorable for the delivery of the drug in the treatment of tuberculosis [34]. Polyesters of inulin with various carboxylic acids, obtained by chemical synthesis, demonstrated excellent properties for paint compositions as a binder [35].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that doxorubicin conjugated to soluble inulin using a carboxymethylation method enabled the cytotoxic response to be maintained or improved at lower doses as compared to free doxorubicin [27]. The key advantages of using inulin particles in MPI rather than free soluble inulin, which was reported by Peppas and colleagues in 2013 [27], could further help drug conjugate effectiveness by preventing rapid renal excretion, increasing the biological half-life, and enabling uptake of the injected MPI particles by monocytes with subsequent selective tissue transport to lymphoid organs [28,29]. Consequently, we hypothesized that MPI might be a promising targeted drug delivery vehicle for immune cell cancers, such as myeloid leukemias.…”
Section: Introductionmentioning
confidence: 99%